Inhibition of high-voltage-activated calcium currents by acute hypoxia in cultured retinal ganglion cells - Dumanska, Hanna; Telka, Mariia; Veselovsky, Nikolai (Frontiers in Cellular Neuroscience, 2023)
Hypoxia is a common factor of numerous ocular diseases that lead to dysfunctions and loss of retinal ganglion cells (RGC) with subsequent vision loss. High voltage-gated (HVA) calcium channels are the main source of calcium entry into neurons. Their activity plays a central role in different signaling processes in health and diseases, like enzyme activation, gene transcription, synaptic transmission, or the onset of cell death. The aim of this study is to establish and evaluate the initial effect of the early stage of acute hypoxia on somatic HVA calcium currents in cultured RGC. HVA calcium currents were recorded in RGCs using the whole-cell patch-clamp technique in voltage-clamp mode. The fast local superfusion was used for brief (up to 270 sec) application of the hypoxic solution (pO2 < 5 mmHg). The switch from normoxic to hypoxic solutions and back was less than 1 sec. The HVA calcium channel activity was inhibited by acute hypoxia in 79 % of RGCs (30 of 38) in a strong voltage-dependent manner. The level of inhibition was independent of the duration of hypoxia or repeated applications. The hypoxia-induced inhibition of calcium currents had a strong correlation with the duration of hypoxia and showed the transition from reversible to irreversible at 75 sec of hypoxia and longer. The results obtained are the first demonstration of the phenomena of HVA calcium current inhibition by acute hypoxia in RGCs and provide a conceptual framework for further research.